1973
DOI: 10.1136/gut.14.5.354
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle blood flow and neurovascular reactivity in liver disease

Abstract: SUMMARY There was no significant difference in forearm muscle blood flow, measured by the clearance of 133Xenon when 38 patients with liver disease were compared with 38 normal subjects. Patients with a clinically hyperdynamic circulation, finger clubbing, and previous portocaval anastomoses were included in the study.The changes in forearm skeletal muscle blood flow and pulse rate caused by a head-up tilt of 70 degrees were measured in 15 patients with chronic liver disease and 15 age-matched controls. Head-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…It has been suggested that patients with cirrhosis have impaired baroreceptor-mediated sympathetic nervous reactivity (10). The present results do not indicate a general defect in NE-mediated vasoconstriction in these patients as they were able to maintain arterial blood pressure during tilting and the kidney vasculature even capable of further contraction.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It has been suggested that patients with cirrhosis have impaired baroreceptor-mediated sympathetic nervous reactivity (10). The present results do not indicate a general defect in NE-mediated vasoconstriction in these patients as they were able to maintain arterial blood pressure during tilting and the kidney vasculature even capable of further contraction.…”
Section: Discussionmentioning
confidence: 50%
“…an elevated plasma volume (1, 2), cardiac output (3, 4), heart rate (5, 6), and possibly muscle perfusion (6) whereas arterial blood pressure (1, 5) and renal blood flow (5, 7,8) are decreased. The mechanisms of changes in vascular resistance in cirrhosis are unknown.The rise in heart rate during various autonomic reflex stimulation tests has been found significantly reduced in cirrhosis (9), and impaired vasoconstriction in skin and muscles during a vertical tilt has been demonstrated even in patients with compensated cirrhosis (10). It has been…”
mentioning
confidence: 98%
“…The parallel increase of norepinephrine and arterial pressure after tilting suggests that the adrenergic system can achieve an ade quate vascular response in the short term, and a reduced activity of baroreceptors [4] is therefore unlikely. The lack of heart rate ac celeration after tilting could be due to a pre valent peripheral adrenergic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative means of assessing adrenergic responsiveness is by reflex stimu- lation of the sympathetic nervous system. The pressor response to head-up tilt is reported as impaired (21,22) or unimpaired (23).…”
Section: Discussionmentioning
confidence: 98%